- Drava River Flooding in Varaždin and Koprivnica Parts of Podravina (Drava River Region – Between Croatia and Hungary) in the Period 17th-19th Century, Podravina - Petrić, Hrvoje (Array, 2007)
In this paper, the authors speak of Drava River flooding in the area of Varaždin's and Koprivnica's Podravina during the 17th, 18th and 19th centuries, placing this micro region into a wider, Central European context. The first detailed plans for Drava regulation are brought up, originally dating back to late 18th century. Regulations were needed to keep the local population safe from relatively frequent flooding, which brought significant danger. Drava water regulation was so important, as flooding brought harsh consequences. For example, 19th century flooding affected the population so some people, living in areas along Drava, were forced to move across the river to vicinity of today's village of Gola. Additionally, flooding had impact on administrative changes, so 1829/1830 flooding cased the village of Drnje to lose a number of administration functions, which were moved to the nearby village of Peteranec, safely away from river flooding.